Collimator rotation in volumetric modulated arc therapy for craniospinal irradiation and the dose distribution in the beam junction region. Issue 1 (December 2015) - Li, Qilin; Gu, Wendong; Mu, Jinming; Yin, Wenming; Gao, Min; Mo, Juncong; Pei, Honglei
Abstract Purpose The purpose of this study was to investigate the role of beam collimator rotation in Volumetric Modulated Arc Therapy (VMAT) for craniospinal irradiation (CSI), and the impact on dose distribution in the beam junctions. Methods Six adult patients were selected for the study. Six VMAT plans with different collimator angles were generated for each patient. The patients were treated in supine position with two beam isocenters. The plans were evaluated by analysis of Dose-Volume Histogram (DVHs) data for planning target volume (PTV) and organs at risk (OAR), and conformity index (CI) and homogeneity index (HI) for the target. Dose distributions in the beam junctions were examined carefully and experimentally validated in phantom, with measurement using an ion chamber array and film. Results The mean values of HI and CI for the plans with different beam collimator angles were not significantly different. The numbers of segments, monitor units (MUs) and the delivery time of the plans with 45° beam collimator were obviously higher than those in plans with other beam collimator angles. When collimator angle for both sets of beams were set at 0°, there was a 1 mm low dose gap measured in the junction region. Conclusions By setting the collimator angle to 45°, only two isocenters were needed for the treatment of a target with the length up to 90 cm. The HI and CI of the plans were almost the same, regardless if the collimator angles were at 0°. The collimator angles for at least one set of beams should be off 0° in order to avoid a dose gap in the beam junction region.